2001
DOI: 10.1017/s0954579401003066
|View full text |Cite
|
Sign up to set email alerts
|

Low cortisol and a flattening of expected daytime rhythm: Potential indices of risk in human development

Abstract: Since the work of Hans Selye, stress has been associated with increased activity of the limbic–hypothalamic– pituitary–adrenocortical (LHPA) axis. Recently, a number of studies in adults have shown that this neuroendocrine axis may be hyporesponsive in a number of stress-related states. Termed hypocortisolism, the paradoxical suppression of the LHPA axis under conditions of trauma and prolonged stress presently challenges basic concepts in stress research. Adverse conditions that produce elevated cortisol leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

58
743
6
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 797 publications
(818 citation statements)
references
References 7 publications
(8 reference statements)
58
743
6
2
Order By: Relevance
“…A circadian rhythm of cortisol was defined as a sufficient decline in the saliva concentration from morning to afternoon and evening (Santiago et al, 1996). Absence of the expected morning surge, leaving a flat basal secretion pattern, is, in man, associated with severe or prolonged stress and certain psychopathologic states (review by Gunnar and Vazquez, 2001). In pigs, such blunted cortisol curves have been reported in conditions associated with behavioural signs of stress, that is, tethering (Barnett et al, 1987;Janssens et al, 1995) and crowded housing without substrate (de Jong et al, 1998 and.…”
Section: Discussionmentioning
confidence: 99%
“…A circadian rhythm of cortisol was defined as a sufficient decline in the saliva concentration from morning to afternoon and evening (Santiago et al, 1996). Absence of the expected morning surge, leaving a flat basal secretion pattern, is, in man, associated with severe or prolonged stress and certain psychopathologic states (review by Gunnar and Vazquez, 2001). In pigs, such blunted cortisol curves have been reported in conditions associated with behavioural signs of stress, that is, tethering (Barnett et al, 1987;Janssens et al, 1995) and crowded housing without substrate (de Jong et al, 1998 and.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study based in Jamaica, stunted children had levels of cortisol similar to nonstunted children but higher heart rates, and there was also a tendency for the stunted children to have blunted responsivity (Fernald & Grantham-McGregor, 2002). The flattening of cortisol responsivity has been reported in children living under adverse circumstances (Gunnar & Vasquez, 2001). Blunted cortisol responsivity, sometimes accompanied by low daytime values, has been termed 'hypocortisolism', and has been reported under conditions of trauma and prolonged stress (Heim et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Following the onset of a stressor, it usually takes about 10-15 min to produce a rise in circulating cortisol levels; about 20-30 min after the stressor, peak concentrations of cortisol are found in saliva (Klimes-Dougan et al 2001). Following this peak, the negative feedback loop of the LHPA axis begins to reestablish homeostatic functioning by reducing the level of circulating cortisol (Gunnar and Vazquez 2001).…”
Section: Voluntary and Involuntary Responses-mentioning
confidence: 99%
“…Recent research examining responses to social challenges (i.e., public speaking tasks, parent-child conflict discussion tasks, or peer-rejection simulations) has shown that adolescents and children who maintained high levels of cortisol or displayed strong task-related decreases demonstrated greater levels of internalizing and externalizing behavior (Granger et al 1994;Klimes-Dougan et al 2001;Schmidt et al 1999). Although these studies have focused exclusively on cortisol reactivity in response to a specific task, other studies have found that chronic activation of the L-HPA system from continued exposure to stress may alter an individual's reactivity profile, increasing the likelihood of experiencing hypo-or hypersecretion in response to future stressors (Gunnar and Vazquez 2001;Kendall-Tackett 2000). Exposure to stress again (e.g.…”
mentioning
confidence: 99%